Implications Of Lion Group's Non-Compliance In Reporting Changes In Airfare Policies To Monopolistic Practices And Unfair Business Competition In The Aviation Industry - Marcelino Januar; Muhammad Agung; Dinda Yusuf Tsary Arrofi; Elisatris Gultom; Helza Nova Lita (Jurnal Impresi Indonesia, 2024)
The aviation industry in Indonesia plays an important role in supporting community mobility and the national economy. However, non-compliance with regulations, especially in reporting changes in ticket fare policies, has the potential to create monopolistic practices and unfair business competition. One of the cases that emerged was Lion Group's non-compliance which had an impact on the structure of the domestic aviation market. This study aims to analyze the implications of Lion Group's non-compliance with fare regulations on business competition in the aviation industry. The approach used is juridical-normative with data collection techniques through literature studies. The data analyzed includes laws and regulations, legal decisions, and related literature. The results of the study show that Lion Group's non-compliance creates barriers for competitors, reduces consumer choice, and increases the risk of unhealthy market dominance. This violates the principles of Law Number 5 of 1999 concerning the Prohibition of Monopolistic Practices and Unhealthy Business Competition. The implications of this study show the urgency of strengthening regulation and supervision by the Business Competition Supervisory Commission (KPPU) to prevent similar violations. Transparency in tariff policies and commitment to regulation are needed to create healthy and fair competition in the aviation industry. This non-compliance has much greater implications than just an internal problem of the company. This also has an impact on monopolistic practices and unfair business competition that can harm consumers and other business actors. In this context, business competition law, especially Law No. 5 of 1999 concerning the Prohibition of Monopoly Practices and Unfair Business Competition, is important to maintain healthy competition. Non-compliance with the reporting of these tariff changes not only has the potential to lead to competitive unfairness, but can also exacerbate market dominance by a single company, thereby suppressing the diversity of choices for consumers. Through this study, the legal and economic implications of Lion Group's non-compliance with tariff reporting provisions in the business competition law will be analyzed. The author will also examine the extent of its impact on business competition in the Indonesian aviation industry, as well as the steps that can be taken by the relevant authorities to prevent monopolistic practices and promote fair competition. This study aims to provide a deeper understanding of the importance of compliance with fare regulations in creating a healthy and sustainable business climate in the aviation industry.